A Beautiful mind - Howard, Ron (DreamWorks Pictures, 2001)
A brilliant mathematician John Nash, on the brink of international acclaim when he become entangled in mysterious conspiracy. Now only his devoted wife can help him in this powerful story of courage, passion and triumph.